High Prevalence of Malaria Parasitemia and Anemia among Hospitalized Children in Rakai, Uganda - Kiggundu, Valerian L.; O'Meara, Wendy P.; Musoke, Richard; Nalugoda, Fred K.; Kigozi, Godfrey; Baghendaghe, Enos; Lutalo, Tom; Achienge, Marion K.; Reynolds, Steven J.; Makumbi, Fred; Serwadda, David; Gray, Ronald H.; et al. (PloS one, 2013)
There is a paucity of data on malaria among hospitalized children in malaria endemic areas. We determined the prevalence, presentation and treatment outcomes of malaria and anemia among children in two hospitals in Rakai, Uganda. Children under five years hospitalized in Kalisizo hospital or Bikira health center in Rakai district, Uganda between May 2011 and May 2012 were enrolled and followed-up until discharge, death or referral. Data were collected on social-demographic characteristics, current and past illnesses and clinical signs and symptoms. Blood smears, hemoglobin (Hgb) levels and HIV testing were performed from finger/heel prick blood. The associations between malaria infection and other factors were estimated using log-binomial regression to estimate adjusted prevalence risk ratios (aPRR) and 95% confidence intervals (CIs), controlling for clustering at health facilities. 2471 children were enrolled. The most common medical presentations were fever (96.2%), cough (61.7%), vomiting (44.2%), diarrhea (20.8%), and seizures (16.0%). The prevalence of malaria parasitemia was 54.6%. Children with malaria were more likely to present with a history of fever (aPRR 2.23; CI 1.18-4.24) and seizures (aPRR 1.12; CI 1.09-1.16). Confirmed malaria was significantly lower among girls than boys (aPRR 0.92; CI 0.91-0.93), HIV infected children (aPRR 0.60 CI 0.52-0.71), and children with diarrhea (aPRR 0.76; CI 0.65-0.90). The overall prevalence of anemia (Hgb<10 g/dl) was 56.3% and severe anemia (Hgb<6 g/dL) was 17.8%. Among children with severe anemia 76.8% had malaria parasitemia, of whom 93.1% received blood transfusion. Malaria associated mortality was 0.6%. There was a high prevalence of malaria parasitemia and anemia among inpatient children under five years. Malaria prevention is a priority in this population.